A qualitative study of the views of women aged 18-29 on over-the-counter availability of hormonal emergency contraception. Issue 4 (1st October 2001) - Folkes, Liz; Graham, Anna; Weiss, Marjorie
Abstract : Objective: To explore women's views on the deregulation of hormonal emergency contraception (EC) prior to it becoming deregulated on 1 January 2001. Design: Qualitative study using face to face, semi-structured interviews. Setting: A NHS family planning clinic, a voluntary sector family planning clinic and a general practice in the South West region. Subjects: Twenty-seven women aged 18-29 years. Results: Most women were in favour of deregulation with over-the-counter provision perceived as quick, convenient and anonymous. Reservations regarding overuse and over-reliance upon EC mirror those of health professionals, although it was not felt that the increased accessibility of EC would lead to changes in sexual activity. Concerns that deregulation would promote an irresponsible attitude towards contraception were largely focused on younger women. Cost was generally regarded as a positive barrier to overuse. However, it was felt that the price should not be prohibitively high. A figure corresponding to the current prescription charge was most often cited. The pharmacy was the preferred choice of provider for most women. Conclusion: Although most women in this study would prefer to obtain EC over-the-counter, the current charge of £20 is likely to prove a barrier.